PENYEBAB CHANGE ORDER PROYEK KONSTRUKSI RUMAH SAKIT - Daniel Daniel; Mega Waty (JMTS: Jurnal Mitra Teknik Sipil, 2023)
The number of hospital construction projects in Indonesia continues to grow. The main reason is because Indonesia's territory is getting denser, so it is necessary to develop supporting facilities to keep up with this development. In a construction project there are three important things in a construction project to focus on, namely quality, cost and time. In order for these three important elements to be carried out, an agreement must be made which must be agreed upon and regulated by the parties involved in accordance with the applicable provisions and in the form of a contract. In a project there may be a change in the contract caused by several predictable and unexpected variables, these changes are known as change orders. Change orders are common and unavoidable in every construction project, both government construction projects and private construction projects. To reduce the occurrence of change orders, it is necessary to know the factors that cause changes in contracts in hospital construction projects. Factors that cause change orders are compiled into a questionnaire to find out the main causes of change orders. Questionnaires were distributed to owners, consultants and contractors who are experienced in hospital construction projects in the Bandung area. This questionnaire will be processed using the Partial Least Square method and using the smartPLS 3.0 application. It was found that the construction factor affected the change order in hospital construction projects with a path coefficient value of 0.702 or 70.2%. Abstrak Jumlah proyek konstruski rumah sakit di Indonesia terus berkembang. Alasannya dikarenakan wilayah Indonesia yang semakin padat, dan dibutuhkanlah pengembangan fasilitas-fasilitas pendukung untuk mengikuti perkembangan tersebut. Pada proyek konstruksi terdapat tiga hal penting yang menjadi fokus, yaitu mutu, biaya dan waktu. Agar ketiga unsur itu dapat terwujud, dibuat suatu kontrak yang disepakati dan diatur oleh pihak yang terlibat sesuai dengan ketentuan yang berlaku. Pada suatu proyek bisa terjadi perubahan kontrak yang disebabkan oleh beberapa variabel terduga maupun variabel yang tidak terduga, perubahan tersebut dikenal dengan istilah change order. Change order merupakan hal umum dan tidak dapat dihindari dalam setiap proyek konstruksi, baik proyek konstruksi pemerintah maupun proyek konstruksi swasta. Untuk mengurangi terjadinya change order, maka perlu mengetahui faktor penyebab perubahan kontrak pada proyek konstruksi rumah sakit. Faktor penyebab change order disusun menjadi kuesioner guna mengetahui penyebab utama dari change order. Penyebaran kuesioner dibagikan kepada para pemilik, konsultan, serta kontraktor yang berpengalaman dalam proyek konstruksi rumah sakit di wilayah Bandung. Kuesioner ini diolah dengan menggunakan metode Partial Least Square dan menggunakan aplikasi smartPLS 3.0. Diperoleh bahwa faktor  konstruksi berpengaruh terhadap change order pada proyek konstruksi rumah sakit dengan nilai path coefficient sebesar 0,702 atau 70,2%.